Similar causes of various reproductive disorders in early life - Konstantin Svechnikov; Jan-Bernd Stukenborg; Iuliia Savchuck; Olle Söder (Asian Journal of Andrology, 2014)
During the past few decades, scientific evidence has been accumulated concerning the possible adverse effects of the exposure to environmental chemicals on the well-being of wildlife and human populations. One large and growing group of such compounds of anthropogenic or natural origin is referred to as endocrine-disrupting chemicals (EDCs), due to their deleterious action on the endocrine system. This concern was first focused on the control of reproductive function particularly in males, but has later been expanded to include all possible endocrine functions. The present review describes the underlying physiology behind the cascade of developmental events that occur during sexual differentiation of males and the specific role of androgen in the masculinization process and proper organogenesis of the external male genitalia. The impact of the genetic background, environmental exposures and lifestyle factors in the etiology of hypospadias, cryptorchidism and testicular cancer are reviewed and the possible role of EDCs in the development of these reproductive disorders is discussed critically. Finally, the possible direct and programming effects of exposures in utero to widely use therapeutic compounds, environmental estrogens and other chemicals on the incidence of reproductive abnormalities and poor semen quality in humans are also highlighted.